Manage Insurance Customer Satisfaction with Premiums and Perceived Quality Assessments. - M. Rizqi Padma Negara; Zaenal Aripin; Kosasih (Journal of Jabar Economic Society Networking Forum, 2023)
The competition among insurance companies is getting fiercer. The development of the industry today is very competitive; this can be seen from a large number of people in industries with enormous potential in the current era, with developments causing competition in similar industries. This study determines whether customer satisfaction can be achieved with affordable premium prices and good service quality. (Basic method of quantitate active approach, Respondents use questionnaire random sampling method to insurance customers, sampling through primary and secondary techniques, Data quality test instrument, Data processing procedure using SPSS (Statistical Package for Social Sciences) 26.0) To find out the quality of service, find out the affordable premium price and its effect on customer satisfaction of insurance services, find out the affordable premium price and its impact on insurance customer satisfaction. Their analysis results that Service Quality (X1) is positively related to Customer Satisfaction, increasing by 44.4%. In addition, Premium (X2) is also positively associated with Customer Satisfaction, rising by 19.9%. Overall, Service Quality (X1), Premium (X2), and Customer Satisfaction (Y) significantly affect each other. Customer satisfaction is influenced by two main factors, namely premium price and service quality. Affordable premium prices make people interested in using insurance policies, especially if the Premium than Premium is higher than the value of other insurance. In addition, service quality also plays a critical essential influencing customer satisfaction. Insurance marketers must be responsive in handling customer complaints and be friendly and polite. Good and Excellent office facilities also contribute to customer satisfaction. In addition, is insurance explained in the product clearly and easily understood by customers? By paying attention to these factors, insurance companies can increase customer satisfaction and gain a competitive advantage in the market.